2010
DOI: 10.3164/jcbn.09-97
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Paraquat-Induced Oxidative Stress on Insulin Regulation of Insulin-Like Growth Factor-Binding Protein-1 Gene Expression

Abstract: Oxidative stress is thought to play a role in the development of insulin resistance. In order to elucidate the molecular effect of oxidative stress on liver insulin signaling, we analyzed the effect of paraquat (1,1-dimethyl-4,4-dipyridynium; PQ)-derived oxidative stress on the expression of insulin-dependent genes and activation of liver insulin signaling pathway. Incubation of primary cultured rat hepatocytes with 2 mM PQ for 6 h impaired the suppressive effect of insulin on insulin-like growth factor-bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…6). The transcription of Igfbp-1 in liver is repressed by insulin, and this repression is impaired by oxidative stress due to the interruption of insulin-dependent phosphorylation of mammalian target of rapamycin (Kimura et al , 2010). Therefore, the increased mRNA of Igfbp-1 in Nrf2-null mice could be due to the more oxidative cellular environment in their hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…6). The transcription of Igfbp-1 in liver is repressed by insulin, and this repression is impaired by oxidative stress due to the interruption of insulin-dependent phosphorylation of mammalian target of rapamycin (Kimura et al , 2010). Therefore, the increased mRNA of Igfbp-1 in Nrf2-null mice could be due to the more oxidative cellular environment in their hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Igfbp1 significantly increased in the DEN-I3C group and decreased in the DEN-I3C-NAC group compared to the DENalone group. Kimura et al (2010) reported that Paraquatinduced oxidative stress increased Igfbp1, while addition of NAC treatment decreased Igfbp1 in rat hepatocytes. Therefore, fluctuations of Glrx1and Igfbp1 in the present study indicate that oxidative stress is enhanced by the I3C treatment, but is directly depressed by NAC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this stage, nitric oxide NObinds with O2resulting in peroxynitrite ONOO - (14). The state of oxidative stress plays a role in the creation of insulin resistance (15) which can be explained as a result of the inhibitory action of ROS on the gene of insulin receptors in addition to the destructive action of ROS on molecules that promotes insulin secretion (16). Also there will be an impeding in glucose entry to the cells (17).…”
Section: Discussionmentioning
confidence: 99%